Investigation of Emotional Intelligence, Self-Efficacy, and Perceived Organizational Support as Enablers of Subjective Well Being - Renalwin Sitorus; Paramitha Messayu; Aisyah Pia Asrunputri; Sarfilianty Anggiani (Agregat: Jurnal Ekonomi dan Bisnis, 2023)
With the everchanging business environment, organization must revisit the way their approach they employee. It is imperative to think ways to provide happiness for employees. The researchers chose to investigate emotional intelligence, self-efficacy, and perceived organizational support as enablers of subjective well-being using 263 samples of Indonesian workers and employs purposive sampling as the sampling technique. The result shows that: (1) Emotional intelligence has a positive and significant influence on subjective well-being; (2) self-efficacy shows a negative and insignificant influence on subjective well-being; (3) perceived organizational support has a positive correlation with insignificant influence on subjective well-being.